2016
DOI: 10.1111/1750-3841.13424
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Protein Profile from Drip Loss in Relation to Pork Quality

Abstract: The aim of this research was to correlate the sarcoplasmic protein profile of the natural drip loss of muscle with the technological and sensory quality of pork meat. Material for analysis was taken from 14 PenArLan pigs. Simple analysis of relationships between the test protein and meat quality traits showed that they adopt a range of from -0.58 to 0.72. It has been shown that the significance of glycolysis expressed as level of glycogen and lactic acid may be 86% (coefficient of correlations, C = 0.93), expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
(109 reference statements)
2
14
0
Order By: Relevance
“…Significant correlation between the content of the ALD and the level of lactate in pork muscle was found by Grzywacz (). The results in the presented study are also in agreement with the work of Przybylski, Kaczor, et al (), which showed significant relationship between colour parameter (L* lightness) and ALD. This enzyme plays an important role in the final reaction of the first stage of glycolysis in the aldol cleavage reaction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significant correlation between the content of the ALD and the level of lactate in pork muscle was found by Grzywacz (). The results in the presented study are also in agreement with the work of Przybylski, Kaczor, et al (), which showed significant relationship between colour parameter (L* lightness) and ALD. This enzyme plays an important role in the final reaction of the first stage of glycolysis in the aldol cleavage reaction.…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon could be explained partially by the analysis of protein profile in drip loss. Di Luca, Elia, Mullen, and Hamil () and Przybylski, Kaczor, et al () showed that muscle exudate provides valuable information about post‐mortem changes which occur in muscle tissue during ageing period and gives the possibility of better understanding the process of conversion of muscle into meat. The protein profile in the presented study was similar to the one obtained by Żelechowska, Przybylski, Jaworska, and Santé‐Lhoutellier ().…”
Section: Discussionmentioning
confidence: 99%
“…Whereas LDH catalyzes the last step of the glycolytic pathway, i.e., the conversion of pyruvate to lactate. In a study conducted by Przybylski et al (2016), a significant correlation (r = 0.58) was observed between ALD and color parameters. However, Gao et al (2016) demonstrated a significant correlation between redness (a * value) of sheep cardiac muscle and CK.…”
Section: Correlation Between Sarcoplasmic Proteins and Some Meat Qualmentioning
confidence: 95%
“…Natural proteins with excellent biological characteristics attracted the attention of many nutritionists, such as the duck meat, chicken, beef, pork, and other livestock industry development provides a rich protein source for human nutrition (Przybylski et al, ; Wang et al, ; Wen et al, ; Zeng, Bai, Zhu, & Dong, ; Zhao et al, ). In recent years, active proteins and peptides from natural resources exhibiting potent antioxidative activities have been investigated for potential use as food additives (Xue et al, ).…”
Section: Introductionmentioning
confidence: 99%